Diels–Alder reactions in confined spaces: the influence of catalyst structure and the nature of active sites for the retro-Diels–Alder reaction - Cantín, Ángel; Gomez, M. Victoria; de la Hoz, Antonio (Beilstein Journal of Organic Chemistry, 2016)
Diels–Alder cycloaddition between cyclopentadiene and p-benzoquinone has been studied in the confined space of a pure silica zeolite Beta and the impact on reaction rate due to the concentration effect within the pore and diffusion limitations are discussed. Introduction of Lewis or Brønsted acid sites on the walls of the zeolite strongly increases the reaction rate. However, contrary to what occurs with mesoporous molecular sieves (MCM-41), Beta zeolite does not catalyse the retro-Diels–Alder reaction, resulting in a highly selective catalyst for the cycloaddition reaction.
Keywords: catalysis; Diels–Alder; retro-Diels–Alder; zeolites